COAGULOPATHY ASSOCIATED WITH COVID-19 IN PATIENTS INFECTED WITH SARS-COV-2. (Ustozlar uchun, 2025)
Coronavirus infection (COVID-19), considered an acute infectious disease caused by the SARS-CoV-2 virus, is characterized by activation of the hemostasis system. As a result of this, severe cases can develop coagulopathy. Whether COVID-19 is the direct cause of this condition or whether they occur with the development of an infectious process remains unclear for the time being. The frequency of occurrence of asymptomatic and clinically specific thrombotic, thromboembolic complications in COVID-19 remains uncertain. This condition is largely associated with difficulties in diagnosis. The purpose of the work to study the significance of coagulopathy markers in patients with COVID-19 and their prognostic role in various clinical forms of the disease.